Alternatives for legalizing small-scale mining in the Médio Tapajós Mining Reserve (Research, Society and Development, 2023)
The state of Pará has vast mineral wealth, which has attracted miners and prospectors for decades. This important sector of the regional economy has been gradually maturing and gaining prominence on the national scene. The Tapajós region, in the west of Pará, stands out for its gold production, attracting prospectors since the 1980s. The Médio Tapajós Mining Reserve was created in this region in 1983, with the aim of regulating mining activity in the area. In recent years, the reserve has faced a number of challenges due to the intensification of illegal mining activity and the bureaucratic barriers to legalizing the activity. This study seeks to identify the main challenges to legalizing mining activity in the area of the Médio Tapajós Mining Reserve and to find alternatives to promote economic activity legally in this area, which is rich in minerals. To this end, qualitative and quantitative data was used, collected through bibliographical and documentary research on subjects related to the theme, and the collection of data produced by related public bodies, such as mining processes and cartographic bases. The results showed that the release of the territory of the Médio Tapajós Mining Reserve by the ANM and the possibility of a review of the management plans of the National Forests that overlap the area would be alternatives for the legal exercise of mining activity in the region, with a view to the full use of the principle of sustainable development in that context.